Missing the boat or sinking the boat: a study of new venture decision making - Mullins, John W.; Forlani, David (Journal of Business Venturing, 2005)
Taking two conceptualizations of risk, Dickson and Giglierano's [J. Mark. 50 (1986) 58] nautical analogy of entrepreneurial risk (sinking vs. missing the boat) to represent the likelihood of loss element of new venture risk, and March and Shapira's [Manage. Sci. 33 (1987) 1404] risk as hazard (boat size) to represent the magnitude of loss element of new venture risk, we investigated how two contextual factors, the suitability of entrepreneurs' skills and their sources of funds, and two individual differences factors, the entrepreneurs' risk propensities and their perceptions of risk, influence their new venture decision making. Metaphorically speaking, we found that most entrepreneurs would rather risk missing than sinking the boat, and that they preferred to pilot bigger craft than smaller ones. Perhaps surprisingly, our sample of highly successful entrepreneurs made relatively risk-averse choices, with 83% choosing either of the two ventures for which the chances for loss were lowest. We also found that the source of new venture funding—the entrepreneur's own money versus that of investors—influenced our subjects' choices between ventures whose chances for loss or gain differed. A similar effect was found for the entrepreneur's risk propensity. On the other hand, we found that the risk the entrepreneurs perceived in the choice set also influenced choices, but only where the magnitude of the new venture's potential gain or loss varied. When viewed in total, our study and results suggest a risk- and reward-based typology of new venture opportunities, one that may provide a conceptual foundation for future explorations of a variety of questions relevant for entrepreneurs and theorists alike.